The Neutral Real Interest Rate - Tom Bernhardsen (Norges Bank, 2005)
The topic for this paper is the so called neutral real interest rate. This is frequently defined as the level of the real interest rate consistent with stable inflation and production equal to potential production. Hence the neutral real interest rate is a benchmark for evaluating monetary policy. While the real interest rate should be set above the neutral real interest rate in cyclical upturns, it should take a level below in recessions. In principle then, to be able to assess the degree of policy accommodation, knowing the level of the neutral real interest rate is as important as knowing the real interest rate. Moreover, the neutral real interest rate is not constant over time. In contrast, it depends on the structure of the economy. A decline in the neutral real interest rate implies that, for a given real interest rate, monetary policy is less expansionary. In isolation, a decline in the neutral real interest rate demands a lower nominal interest rate to maintain the monetary policy stance.
hdl:11250/2508136
Keywords: 330